Fly ash as to solidify liquid radioactive waste (2020)
The "Termopaipa" power plant located in Boyaca, Colombia, generates electricity based on coal and whose residue is fly ash. In this study we consider it important to understand its physical, chemical and morphological characteristics to be used for purposes beneficial to the environment and to use them as a solidifier of liquid radioactive waste. The treatment of radioactive waste involves the set of physical and chemical processes that entail the change of some characteristic of the initially generated waste in order to optimize the safety and / or economy of its management. This treatment requires the transformation of the radioactive waste into an acceptable final product for its transport and / or temporary storage and / or definitive storage. This transformation can be carried out through the incorporation of residues in phases such as Mullite and quartz identified by X-ray diffraction, or encapsulation within porous structures present in the ashes observed by scanning electron microscopy and fixation based on an electrostatic interaction mechanism. originated on its surface due to the presence of aluminate and silicate groups identified by X-ray photoelectron spectroscopy.